Implementation of sociopreneurship in women farmers groups (KWT) with utilization of local food to improve food security and family economy - Ermamilia, Aviria; Friday, Lastdes Cristiany; Wisnusanti, Setyo Utami; Rizqi, Farah; Amelia, Safira Tasya; Indriyani, Sinta (Journal of Community Empowerment for Health, 2024)
Introduction: The COVID-19 pandemic has had an impact on the economic and business sectors in Indonesia. The pandemic has affected household food security not only in the economic sector but also in the household sector. The number of households experiencing food insecurity has increased as they cannot meet their food needs. In Sleman Regency, a forum for women farmer's groups (KWT) sells local food. One quite active is in Moyudan and Minggir Region, but the sales are not optimal, and not all have received training. Therefore, this study aims to see changes in KWT's knowledge, improve their marketing after training, and increase their economic status. Methods: This research was conducted in Sleman Regency, DIY. The training target involved the KWT in Moyudan and Minggir Region forums. We collected primary data from KWT characteristics (24 groups) and pre-post-test scores for each training (46 and 27 participants). The activities include 1) socialization of the program and bazaar of KWT products; 2) training of KWT; 3) packaging design and accompaniment; and 4) developing module training. Results: Most of KWT produces dry foods, such as vegetable and fruit chips, and shredded. Most of KWT's businesses (75.0%) are still running, although some have stopped due to difficulty in promotion during the pandemic. The obstacles experienced by KWT were using technology, arranging home industry food permits (P-IRT), and marketing. Training 1 and 2 pre-tests and post-test results increased only a little since the participants already had good knowledge (62.5% and 85.5% mainly answered correctly). However, many participants still answered incorrectly regarding the halal certification and food licensing. Ten KWTs succeeded in designing product logos and were assisted in making new, more attractive designs. Conclusion: The accompaniment can help KWT maximize its potential to improve the community's economic status.